Mixed neuropathology in frontotemporal lobar degeneration. Issue 3 (2nd April 2020) - Pennington, Catherine; Marini, Luca; Coulthard, Elizabeth; Love, Seth
Abstract: Aim : Frontotemporal lobar degeneration (FTLD) is a significant cause of dementia in mid-life and older adults. The extent of interactions between FTLD and other neurodegenerative pathologies is unclear. We reviewed the occurrences of mixed pathology in cases of neuropathologically diagnosed FTLD from the UK Brain Bank Network. Materials and methods : Clinicopathological details of cases of FTLD were extracted from the UK Brain Bank Network database. Results : Of 515 cases, 30.10% had mixed neuropathology. Concordance between clinical and neuropathological diagnosis was lower in these cases (38.71% vs. 59.17%). Alzheimer's spectrum pathology was the commonest additional finding. Age at death was higher in mixed neuropathology cases (mean 76.7 years vs. 72.59.0 years, p < 0.005), increasing in tandem with the number of neuropathologies present. Conclusion : Mixed neuropathology is common in FTLD and associated with increased age at death. Our findings suggest that mixed neuropathology influences age at onset and clinical phenotype in FTLD and makes accurate antemortem diagnosis more difficult. Further investigation of interactions between neuropathologies and phenotype is warranted, particularly in view of the potential impact on clinical diagnosis and patient selection for clinical trials. Key points: Mixed neurodegenerative neuropathologies commonly occur with frontotemporal lobar degeneration. The likelihood of mixed neuropathology with FTLD increases with older age at death. Mixed neuropathology could influence the clinical phenotype of frontotemporal lobar degeneration.